Evaluation of Exogenous Proteases in Broiler Diets - BF Almeida; CH Oliveira; KMM Dias; RD Bernardes; SO Borges; KM Gomes; LP Castro; RV Nunes; AA Calderano (Brazilian Journal of Poultry Science)
ABSTRACT This study aimed to evaluate the effects of different exogenous proteases in broiler diets on performance, metabolizable energy, and the crude protein (CP) digestibility values of diets. A total of 1440, 384, and 432 birds were distributed in a completely randomized design in the performance, metabolism, and digestibility experiments, respectively. The treatments applied to the three experiments were: T1 - positive control (PC; basal diet, 23,23% CP in starter phase and 20,58% CP in grower/finisher phase); T2 - negative control (NC; 18,54% CP in starter phase and 18,46% CP in grower/finisher phase); T3 - NC added with Protease A; T4 - NC added with Protease B; T5 - NC added with Protease C; T6 - NC added with Protease D; T7 - NC added with Protease E; and T8 - NC added with Protease F, plus a treatment with a protein-free diet in the digestibility experiment. Reducing the protein level in the diet reduced BWG and worsened FCR. The proteases did not improve any of the performance parameters evaluated, except for protease C, which improved BWG, but not at a sufficient level to recover the lost performance, and not equal to CP. In addition, there were no differences in the metabolizable energy values. Furthermore, the proteases did not improve the standardized ileal digestibility of crude protein of diets with reduced protein. In conclusion, the supplementation of the tested proteases does not recover the growth performance lost by reducing the crude protein in the diet.